E-procurement for IT stuff / Chua Fong - Chua, Fong (2004)
All undergraduates of the Faculty of Computer Science and Information Technology (FSKTM), University of Malaya are compulsory to take course entitled "Projek Ilmiah Tahap Akhir" in their 3rd year of study. Ilmiah Tahap Akhir brings out 9 credit hours of total 108 credit hours. Projek Ilmiah Tahap Akbir consists of2 component; firstly, WXES3181/WXET3181: Projek Ilmiah Tahap Akhir I (Semester I - 4 credit hours), secondly, WXES3182/WXET3182: Projek Ilmiah Tahap Akhir II (Semester II - 5 credit hours). Content of WXES3181/WXET3181 are mainly bout the explanation of propose project supported by review of literature, paining and design. The name of the propose system is e-Procurement of IT stuff This project aims to develop a online purchase order tracking system which is appropriate for the usage of an organization to simplify their purchasing IT stuff processes such as printer, computer desk, mouse and extra. This system consists of 3 main modules. They are the administrator module, client module and vendor module each has their own functions. Tools planning for system development are in Linux platform, PHP scripting language, JavaScript and DBMS PostgreSQL.